Identification of the Utilization of the Canal Edge Area in Makassar City - Raeny Tenriola Idrus; Armiwaty Armiwaty; Andi Yusdi Dwiasta R; Andi Nur Kalsum Ningki; Nur Hikmah (PINISI Discretion Review, 2023)
The increase in population has an impact on increasing the population's need for housing. Developments that continue to increase have an impact on changing open spaces that should function as open spaces without buildings to change into open spaces with buildings, both permanent and temporary. Increasing development is changing the face of open spaces into residential complexes. As a result, there are no children's play areas and community socialization spaces outside the home, so road infrastructure and canal border areas are chosen as places for community social activities.This study aims to examine the use of space in the residential area on the banks of the Jongaya canal, Pabaeng-baeng subdistrict, based on community social activities, including studying activities along the Jongaya canal inspection road between Andi Tonro Street and Sultan Alauddin Street. This descriptive study uses a cognitive mapping analysis technique, which is a method of analyzing social activities based on spatial use patterns through spatial mapping media and community activities. The result of the research is the mapping of community activities based on the types of activities, time and intervals for the use of social space. Community activities generally use the road for activities.